Adaptation of Potato Varieties of Hungary to the Certain Conditions - Polgar, Zsolt; Тashmatova, М. А.; Kholdarov, М. U.; Lapasov, S. S.; Аripova, Sh. R.; Тursunov, D.; Ismoyilov, О. (International Journal on Integrated Education, 2023)
According to the cooperation agreement between the "Hungarian University of Agriculture and Life Sciences - Potato Research Center" of Hungary and the Ministry of Agriculture of the Republic of Uzbekistan signed in Budapest on February 17, 2021, 6 varieties of Hungarian selection - "Balaton Rossa", "Demon", "Botond", "White", "Balatoni Sarga" potato variety samples were brought for testing in the soil and climate conditions of our Republic and were carried out in the experimental field of the institute in the Tashkent region, Bostonliq district and Samarkand. was tested at the station. In this article, in the test results, Hungarian potato varieties "Balatoni Rossa", "Demon", "Botond", "White", "Balatoni Sarga" gave excellent results. The results of scientific research on the establishment of primary seed production of "Balatoni Sarga" varieties are presented.